Characterization of a Mixture of Oca (Oxalis tuberosa) and Oat Extrudate Flours: Antioxidant and Physicochemical Attributes - Marisol P. Castro-Mendoza; Heidi M. Palma-Rodriguez; Erick Heredia-Olea; Juan P. Hernández-Uribe; Edgar O. López-Villegas; Sergio O. Serna-Saldivar; Apolonio Vargas-Torres (Journal of Food Quality)
The oca (Oxalis tuberosa) is a tuber with high starch content and excellent antioxidant properties, which can be used in the production of extruded products; however, starch-rich products can be improved nutritionally through the incorporation of fibers that can result in extrudates with beneficial health properties. The aim of this work was to develop a mixture of oca (Oxalis tuberosa) and oat extrudate flours and evaluate the antioxidant and physicochemical attributes. The results showed that a higher moisture content increased the hardness, water absorption index, and density of the extrudates; however, the solubility and expansion indexes showed an inverse pattern. The addition of oat fiber had the opposite effect from moisture content on the physicochemical properties mentioned above. The cellular antioxidant activity (CAA) of the extrudates decreased when the oat fiber increased. An inverse pattern was observed when the moisture concentration was increased. The starch hydrolysis percentage and glycemic index decreased significantly when the fiber content increased. Oat fiber contributed 67.29% and 65.04% to these parameters, respectively. Oat fiber exerted a greater effect than moisture on the collets extruded in this study according to factor contributions.